2022
DOI: 10.1021/jacs.1c13041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Principles of Redox-Coupled Protonation Dynamics in Photosystem II

Abstract: Photosystem II (PSII) catalyzes light-driven water oxidization, releasing O 2 into the atmosphere and transferring the electrons for the synthesis of biomass. However, despite decades of structural and functional studies, the water oxidation mechanism of PSII has remained puzzling and a major challenge for modern chemical research. Here, we show that PSII catalyzes redox-triggered proton transfer between its oxygen-evolving Mn 4 O 5 Ca cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
77
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 87 publications
(309 reference statements)
12
77
2
Order By: Relevance
“…Although the present O 2 end -on configuration differs from the typical side -on coordination in Ni-O 2 complexes of other dioxygenases, the proposed O 2 – splitting process resembles a Criegee rearrangement in non-heme iron intradiol dioxygenases, as well as an alkylperoxo-intermediate observed in extradiol-ring cleaving dioxygenases . Moreover, similar peroxo-intermediates have been proposed for O–O bond splitting in oxidoreductases like cytochrome c oxidase or apocarotenoid oxygenase (see Figure S10 for comparison to AsqJ), as well as in enzymatic and molecular H 2 O-splitting catalysts, such as photosystem II , and Ru-catalysts, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Although the present O 2 end -on configuration differs from the typical side -on coordination in Ni-O 2 complexes of other dioxygenases, the proposed O 2 – splitting process resembles a Criegee rearrangement in non-heme iron intradiol dioxygenases, as well as an alkylperoxo-intermediate observed in extradiol-ring cleaving dioxygenases . Moreover, similar peroxo-intermediates have been proposed for O–O bond splitting in oxidoreductases like cytochrome c oxidase or apocarotenoid oxygenase (see Figure S10 for comparison to AsqJ), as well as in enzymatic and molecular H 2 O-splitting catalysts, such as photosystem II , and Ru-catalysts, respectively.…”
Section: Discussionsupporting
confidence: 58%
“…Structural elucidation and mechanistic investigations over the past decade have made remarkable progress in understanding the underlying chemical principles of water oxidation occurring in the OEC. A tight coupling of the Kok–Joliot cycle with ligand acid–base chemistry and metal valence/structural isomerism has been found to be crucial for the highly regulated progression of a S i state to a higher oxidation state ( S i +1 ). For example, an extended, seven-step catalytic cycle has been proposed in which ligand deprotonation and metal oxidation events are strictly alternating to prevent a significant increase of the redox potential of the Mn cluster. , At least two isomers with different spin states are likely to be involved in the S 1 , S 2 , and S 3 states, . Two S 1 isomers ( g = 4.8 and 12 in parallel mode) observed by electron paramagnetic resonance (EPR) spectroscopy may differ in a crucial electronic structure feature that is relevant for catalytic progression to the next S 2 state .…”
Section: Introductionmentioning
confidence: 99%
“…The redox isomerism in H + -depleted S 2 state results in either Mn oxidation state (4443) for the open cubane ( S 2 Y Z • ) or (4444) for the closed cubane ( S 3 Y Z ) . The cluster can, therefore, pick up a new water molecule at either Mn D III of the open cubane or Mn A IV of the closed cubane, leading to two mutually exclusive propositions: water binding first (open cubane) ,, and Mn oxidation first (closed cubane) ,, mechanisms for the S 2 to S 3 transition. Because of its mechanistic significance, we set out to perform a detailed mechanistic study using broken-symmetry (BS) density functional theory (DFT) followed by the generalized spin projection technique, , with an aim of comprehending the functional roles of the flexible primary coordination sphere in the H + -depleted S 2 state and in the decay of the S 3 state to a modified S 2 state.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] The quantum chemical simulations by Kaila and coworkers on PS II revealed that the electric field generated during the oxidation of redoxactive Tyr161 has a significant effect on lowering the energy barrier for the water-mediated proton transfer from the cluster-bound water molecule to the Asp61 residue, leading to the facile generation of the reactive state. 11 Thus, taking a lesson from nature, it can be perceived that the secondary coordination sphere might play an essential role in developing efficient artificial WOCs.…”
Section: Sukanta Mandalmentioning
confidence: 99%